Experimental investigation of thermal performance of single pass solar collector using high porosity metal foams - Wisam Mohammed Mutar; Yaser Alaiwi (Case Studies in Thermal Engineering, 2023)
The previous literature showed that there have been many studies focusing on some specific aspects of single-pass solar air collectors, such as the effects of the number of passes, the shape of fins, and their effects on thermal performance. Also, the effect of thermal efficiency accompanied by the existence of these fins has been the interest of many studies. A few research types are dealing with using porous materials (Metal foam) to improve thermal performance. Therefore, an experimental apparatus was designed and fabricated to study the effect of Metal Foam (MF) on the performance of solar air collectors. The experiments were held in Iraq, Al Ramadi climate conditions. A comparison of three configurations of absorber plates of solar air heaters with and without MF is presented and evaluated. The results showed that by including MF fins in the absorber plate, the absorber plate's surface area was increased, increasing heat transmission compared to a flat plate (without MF). Moreover, utilizing MF at the tilted angle of 45° (MFθ=45o) increased turbulence intensity, which improved the mixing of cold and hot air. The MFθ=45o layout had the best thermal efficiency of the three employed configurations (94.8%), followed by the MFθ=0o configuration (62.6%) and the flat plate configuration (33.8%), all with the same mass flow rate. Finally, when using MF fins with a tilted angle of 45°, the air temperature differential is bigger compared to MF fins with a tilted angle of 0° or a flat plate collector.